Preliminary conceptual design and analysis of a 100 kWe level Nuclear Silent Thermal‐Electrical Reactor (NUSTER‐100). (21st September 2022) - Huang, Jinlu; Wang, Chenglong; Tian, Zhixing; Guo, Kailun; Su, G. H.; Tian, Wenxi; Zheng, Youqi; Qiu, Suizheng
Summary: To meet the requirements of the unmanned underwater vehicles (UUVs) for the power source, a conceptual design of a 100‐kWe level Nuclear Silent Thermal‐Electrical Reactor (NUSTER‐100) is proposed. The NUSTER‐100 is a 1‐MWt reactor that has been designed to couple with a 100‐kWe thermoelectric generator system. The high temperature sodium heat pipes are adopted to cool the reactor core. The cascaded wide temperature range thermoelectric generation (TEG) system is used to achieve thermoelectric conversion, which ensures high power generation efficiency and low operating noise. The neutronic and thermal‐mechanical analysis results are provided for the design. The core power distribution and energy spectrum are obtained. The neutronic analysis results are imported into ANSYS as input for thermal‐mechanical analysis. In this paper, the fuel‐HPs channel and the 1/8 symmetrical core are selected as the analysis objects, and the temperature distribution and statics parameters under the normal operation condition are obtained. The analysis results show that under normal operation conditions, the core parameters meet the design requirements. These design parameters are all lower than the safety limit. This work provides a certain reference for the design and application of the heat pipe reactor power system.